Coleta seletiva e educação ambiental: desenvolvimento e utilização um aplicativo móvel na implantação da política nacional de resíduos sólidos em um município - Ferreira, Marcos Rogério (2020)
With the enactment of Law 12.305/2010 that instituted the National Solid Waste Policy. And all those responsible, directly or indirectly, for the generation of solid waste to carry out actions related to integrated management or solid waste management are subject to the observation of this law. In this context, selective collection is a fundamental tool for compliance with current legislation. This research analyzes the main laws and decrees that should guide the municipal public managers for the creation of the Municipal Plans for Integrated Management of Solid Waste. This work presents a prototype, for the creation of a mobile application, which can be implemented by public managers and be used as a communication channel between the city and its residents. If planning is based on selective collection, the main actors in this scenario are the citizens, so creating a technology that facilitates communication by presenting a selective collection agenda, specialized collection points and a space to promote environmental education should be a priority.